Survey of impact of gender on emotional intelligence of librarians - Siamak, Marzieh; Haqguyan, Zolfa; Alizadeh, Hamid (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
Purpose: The purpose of this research is to survey the impact of gender on emotional intelligence of librarians of the Qom province state university libraries in Iran.  Statistical Universe: There are sixty librarians working in the Qom province state university libraries of which forty librarians participated in this study. They were selected by using the random sample method. Data were gathered using a standardized questionnaire on emotional intelligence. Finding and Conclusion: Findings showed that emotional intelligence of the librarians included self–awareness, self–motivation, empathy, and social skills. These were considered at an ideal state. Self–regulation in the librarians was shown at an average level. The Freidman test results showed that emotional intelligence varies and the component to the order of priorities were: Self–awareness, empathy, social skills, self– motivation, and self–regulation.